Odpowiedzi

Najlepsza Odpowiedź!
2010-01-12T21:42:17+01:00
A) x + 2y = -13 /*1
x+2y=-13

b) 3x + y = -5 /*2
6x+2y=-10

c) -x + 4y = 2 /*1/2
-1/2x+2y=1

d) x - ½y = 1 /*(-4)
-4x+2y=-4

e) 3x - 3y = 1 /*(-2/3)
-2x+2y=-2/3

f) x + ¾ y = 0 /*8/3
8/3x+2y=8/3
2010-01-12T21:42:46+01:00
A) x + 2y = -13
a=1
b) 3x + y = -5
a=2
6x+2y=-10
c) -x + 4y = 2
a=1/2
-1/2x+2y=2
d) x - ½y = 1
a=4
4x-2y=4
e) 3x - 3y = 1
a=2/3
2x-2y=2/3
f) x + ¾ y = 0
a=2 2/3
2 2/3x*2y=2 2/3

Wszędzie mnożysz równanie przez a :)

2010-01-12T21:50:18+01:00
A)
x + 2y = -13|*1
x+2y=-13

b)
3x + y = -5|*2
6x+2y=-10

c)
-x + 4y = 2|*1/2
-1/2x+2y=1

d)
x - ½y = 1|*(-4)
-4x+2y=-4

e)
3x - 3y = 1|*(-2/3)
-2x+2y=-2/3

f)
x + ¾ y = 0|*8/3
8/3x+2y=0